2018
DOI: 10.1002/jmv.25352
|View full text |Cite
|
Sign up to set email alerts
|

The impact of interferon‐free direct‐acting antivirals on clinical outcome after curative treatment for hepatitis C virus–associated hepatocellular carcinoma: Comparison with interferon‐based therapy

Abstract: Background and Aim To examine the effect on recurrence and survival of treatment by interferon (IFN)‐free direct‐acting antivirals (DAA) for patients with hepatitis C virus (HCV)‐associated hepatocellular carcinoma (HCC) who underwent primary curative treatment. Methods This was a retrospective cohort study of 250 patients with HCV who had received curative treatment for primary HCC. As anti‐HCV treatment after HCC treatment, 38 patients received IFN‐free DAA therapy (DAA patients) and 94 received IFN‐based th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 49 publications
4
23
0
Order By: Relevance
“…Study characteristics were summarised in Tables and . Fifty‐six studies were included, with a total of 5522 patients with HCC, while 27 studies enrolled non‐HCC patients as control groups. Fifty‐three (95%) studies were observational cohorts (45 retrospective and eight prospective) and three studies were clinical trials.…”
Section: Resultsmentioning
confidence: 99%
“…Study characteristics were summarised in Tables and . Fifty‐six studies were included, with a total of 5522 patients with HCC, while 27 studies enrolled non‐HCC patients as control groups. Fifty‐three (95%) studies were observational cohorts (45 retrospective and eight prospective) and three studies were clinical trials.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the time-lag bias, i.e., different time frames applied for recurrence analysis, as seen in Table 3, may lead to discrepant result interpretation. When the follow-up period begins from HCC treatment, it consists of a considerable duration prior to the start of antiviral treatment and counts the period lacking antiviral agents, leading to possible underestimation [23,24,26,[28][29][30]. Furthermore, two of these studies [26,30] firstly included untreated patients as a control group and compared it to IFN-based and DAA arms.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent meta-analysis concluded that the HCC occurrence and recurrence rates were comparable between DAA-and IFN-treated patients regardless of the higher SVR rate of the DAA regimen [10]. Moreover, several reports with single-arm DAA-treated HCV-HCC patients declared abruptly increased HCC recurrence rate after antiviral treatment [11][12][13][14], while conflicting results have been reported in other studies comparing to the untreated [15][16][17][18][19][20][21][22][23][24][25] or IFN-treated groups [10,21,[26][27][28][29][30]. Concerns have been raised about the benefit and the timing of adjuvant DAA-based therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, SVR achieved by IFN-free DAA treatment improved health-related quality of life in patients with chronic HCV infection 9) . Furthermore, SVR achieved by IFN-free DAA treatment suppressed recurrence of HCC and improved overall survival 10) . Thus, increased SVR can provide a lot of benefits for patients with chronic HCV infection, including old-aged patients.…”
Section: Introductionmentioning
confidence: 99%